Ketahanan Masyarakat di Kawasan Pesisir Terdampak Banjir Rob ( Kasus : Desa Timbulsloko, Kecamatan Sayung, Kabupaten Demak ) - , Taufik Perdana Ayunda ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Strengthening the community resilience in disaster-prone areas are needed to to minimize potential of losses and impact from disasters. Sayung is the greatest affected district by tidal flood in Demak. Until 2013, two villages have been relocated due to drowning and not suitable as a place for living. Timbulsloko village that inhabited by 3,265 population have high susceptibility to tidal flood. The aim of this research are : 1.) Projecting the tidal flood area in Timbulsloko